2015
DOI: 10.1007/s00289-015-1480-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a suitable nanostructured cure activator system for polychloroprene rubber nanocomposites with enhanced curing, mechanical and thermal properties

Abstract: Nanostructured zinc oxide (ZnO) and magnesium oxide (MgO) are synthesized by sol-gel method and characterized by X-ray diffraction and fieldemission scanning electron microscopy. The curing characteristics, mechanical, thermal and aging resistance properties of polychloroprene rubber (CR) composites in presence of both nanostructured and conventional cure activators in different combinations are determined. The CR composite containing 2 phr (parts per hundred parts of rubber) nano-ZnO along with 2 phr nano-MgO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Sol-gel-synthesized ZnO and MgO particles were also used to develop a suitable nanostructured cure activator system for CR composites with improved cure, mechanical, and thermal properties. 28 As shown in Figure 13b, a nanostructured cure activator system containing 2 phr nano ZnO along with 2 phr nano MgO had the potential to provide greater torque value than conventional cure activator system containing 5 phr conventional ZnO along with 4 phr conventional MgO in CR formulation. 28…”
Section: B Sol-gel-derived Mgo As Cure Activatormentioning
confidence: 94%
See 1 more Smart Citation
“…Sol-gel-synthesized ZnO and MgO particles were also used to develop a suitable nanostructured cure activator system for CR composites with improved cure, mechanical, and thermal properties. 28 As shown in Figure 13b, a nanostructured cure activator system containing 2 phr nano ZnO along with 2 phr nano MgO had the potential to provide greater torque value than conventional cure activator system containing 5 phr conventional ZnO along with 4 phr conventional MgO in CR formulation. 28…”
Section: B Sol-gel-derived Mgo As Cure Activatormentioning
confidence: 94%
“…During preparation of rubber composites, the quantity of externally added ZnO is expressed in phr. Continuing their research, Roy et al 27,28 reported the preparation of sol-gel-synthesized nano magnesium oxide (MgO)-based rubber composites by conventional two-roll mixing mill process. In those publications, MgO was synthesized by sol-gel auto-combustion method.…”
Section: Preparation Of Sol-gel-derived Materials-based Rubber Compositesmentioning
confidence: 99%
“…The choice of chloroprene rubber (CR) was chosen because of its unique features. CR is a multipurpose synthetic elastomer with a broad industrial application (including wire and cable jacketing, hose, tubes, covers, automotive gaskets, seals, cellular products, construction applications, asphalt modification) due to its high ozone resistance, extraordinary oil and fuel resistance, toughness, good adhesion to other materials, and high heat resistance [ 6 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that modulus and strength properties of ZnO activated sulfur cured polychloroprene rubber with 4% nano‐MgO appeared to have superior properties to the vulcanizate with conventional micro‐ZnO‐activated cure system . Furthermore, polychloroprene rubber (CR) with the mixture of 2 phr of nano‐ZnO and 2 phr of nano‐MgO showed an excellent improvement in curing characteristics ( i.e ., cure time, and cure rate index [CRI]), modulus, and tensile strength, when compared to CR vulcanizate with 5 phr of conventional ZnO and 4 phr of MgO . Moreover, it was found that CaO and MgO might be other appropriate replacements of ZnO in SBR compounds .…”
Section: Introductionmentioning
confidence: 99%